2006
DOI: 10.1080/09585170600682574
|View full text |Cite
|
Sign up to set email alerts
|

Creative teaching and learning in Europe: promoting a new paradigm

Abstract: The tides of globalization and the unsteady surges and distortions in the evolution of the European Union are causing identities and cultures to be in a state of flux. Education is used by politicians as a major lever for political and social change through micro‐management, but it is a crude tool. There can, however, be opportunities within educational experience for individual learners to gain strong, reflexive, multiple identities and multiple citizenship through the engagement of their creative energies. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 3 publications
0
22
0
3
Order By: Relevance
“…Government and university management emphasis upon graduate skills and, in particular, upon the value of critical thinking, is supported by a range of writers who propose that it is central to learning and to the core role of higher education, as well as having a crucial importance for society more generally (Lederer, 2007;Davies, 2006;Facione, Facione and Giancarlo, 2000;Beyer, 1987). In this context, it is no surprise to find that there exists a considerable body of literature on defining and quantifying critical thinking.…”
Section: Critical Thinking: Conceptual Deficit?mentioning
confidence: 99%
“…Government and university management emphasis upon graduate skills and, in particular, upon the value of critical thinking, is supported by a range of writers who propose that it is central to learning and to the core role of higher education, as well as having a crucial importance for society more generally (Lederer, 2007;Davies, 2006;Facione, Facione and Giancarlo, 2000;Beyer, 1987). In this context, it is no surprise to find that there exists a considerable body of literature on defining and quantifying critical thinking.…”
Section: Critical Thinking: Conceptual Deficit?mentioning
confidence: 99%
“…For example, from a study of four one-week-long, in-service development courses for teachers, Davies (2006) found that teaching for creativity was associated with teachers taking a 'long-term view' of a learner's potential, a willingness to wait for results and the confidence to act intuitively at times. From questionnaire data and a series of interviews with teachers (n = 65) and children (n = 390) in primary schools, Grainger et al (2005) conclude that, while all effective teachers reward originality, those who teach for creativity depend on it to enhance their own wellbeing and that of their pupils; they see the development of creativity and originality as the distinguishing mark of their teaching.…”
Section: The Role Of Teachers In Promoting Creative Learning In Pupilsmentioning
confidence: 99%
“…Education systems in many countries aim to develop pupils' creativity (Craft 2005;Davies 2006;Stables 2009), which is seen as important for economic growth through its contribution to a knowledge economy. It is not always easy to tell what is meant by 'creativity' in such education policies; the term has multiple definitions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, developing critical thinking skills can also enhance the ability to draw sound conclusions and make informed decisions (Dwyer, Hogan & Stewart, 2014). By developing graduates with critical thinking skills, universities can enhance innovation in the workplace and society (Davies, 2006;Snyder, 2003). However, many students struggle to understand critical thinking, lack confidence in its application, are unsure how they can develop critical thinking skills and struggle to demonstrate them in their assessments.…”
Section: Introductionmentioning
confidence: 99%